High-Throughput Sequencing Reveals Single Nucleotide Variants in Longer-Kernel Bread Wheat - Chen, Feng; Zhu, Zibo; Zhou, Xiaobian; Yan, Yan; Dong, Zhongdong; Cui, Dangqun (Frontiers in Plant Science, 2016)
The transcriptomes of bread wheat Yunong 201 and its ethyl methanesulfonate (EMS) derivative Yunong 3114 were obtained by next-sequencing technology. Single nucleotide variants (SNVs) in the wheat strains were explored and compared. A total of 5907 and 6287 nonsynonymous SNVs were acquired for Yunong 201 and 3114, respectively. A total of 4021 genes with SNVs were obtained. The genes that underwent nonsynonymous SNVs were significantly involved in ATP binding, protein phosphorylation, and cellular protein metabolic process. The heat map analysis also indicated that most of these mutant genes were significantly differentially expressed at different developmental stages. The SNVs in these genes possibly contribute to the longer kernel length of Yunong 3114. Our data provide useful information on wheat transcriptome for future studies on wheat functional genomics. This study could also help in illustrating the gene functions of the nonsynonymous SNVs of Yunong 201 and 3114.